The Expression of MDM2 Gene Promoted Chondrocyte Proliferation in Rats with Osteoarthritis via the Wnt/β-Catenin Pathway - Jiang, Jiahao; Feng, Shuaihua; Li, Zexiang; Luo, Yangqian; Wang, Zhenyuan; Li, Mingyang; Wu, Guanbao (Cellular and Molecular Biology, 2022)
This study aimed to investigate the regulatory mechanism of MDM2 gene expression on cartilage cell proliferation in Osteoarthritis (OA) rats. For this purpose, 22 SD rats were randomly divided into normal control (10 cases) and treated (12 cases) groups. Treated group was used for OA modelling with the modified Hulth method. After a week, RT-PCR was used to detect MDM2 in cartilage tissue of rats, Wnt 1, Wnt 3 a, Wnt 10 b and β-catenin genes mRNA expression. Rat chondrocytes were isolated and cultured, and the recombinant eukaryotic expression vector pcDNA3.1 myc-siRNA-MDM2-β-catenin and co-expression plasmid pcDNA3.1 myc-siRNA-MDM2-β-catenin was used to transfect chondrocytes and the proliferation and related gene expression levels of the transfected chondrocytes were detected by MTT method and RT-PCR. The results showed that compared with the control group, MDM2, Wnt 1, Wnt 3 a, Wnt 10b and β-catenin genes in OA rat cartilage constructed by Hulth method were increased (p<0.05). The pcDNA3.1 myc-beta-catenin transfection slowed down the proliferation of OA chondrocytes, different from the non-transfected OA group (p<0.001), and increased Wnt 1, Wnt 3a, Wnt 10b and β-catenin genes expression compared with the Control group (p<0.05), but did not affect the expression of MDM2. The transfection of siRNA-MDM2 was opposite to pcDNA3.1 myc-β-catenin. The co-expression plasmid pcDNA3.1 myc-siRNA-MDM2-beta-catenin transfection did not affect the proliferation of OA chondrocytes. In general, the high expression of MDM2 in OA rats restricts the proliferation of chondrocytes, which may be related to the main pathogenesis of the occurrence and development of OA in vivo, and the regulation of MDM2 on the proliferation of chondrocytes may be achieved through the Wnt/ β-catenin pathway.